Mental Relaxation Exercises and Their Effect On Some Immune System Components of Women's Football - Zwayan, Labeeb; Makhlif, Soureen (Journal of Physical Education, 2018)
Mental Relaxation Exercises and Their Effect On Some Immune System Components of Women's FootballThe importance of the research lies in developing some immune system components in female soccer players. The problem lies in the female players having many injuries thus skipping training that negatively affect their performance. The research aimed at identifying the effect of relation exercises on some immune system exercises. The researcher hypothesized significant statistical differences in some Imune system components in posttests between pre and posttests. The researcher used the experimental method. The subjects were (30) female soccer player from Al Jawia club; divided into 11 players for each group and (6) for pilot study and (2) goalkeepers. The tests included trapping and passing, cognitive relation exercises from 10/7/2017 till 3/10/2017 followed by the posttests for both groups. The data was collected and treated using proper statistical operations.